Policy and institutional frameworks: country report Argentina - García, Lila Emilse (2014)
This report offers a brief overview of current Argentine migration policy as it relates to its emigrants. In 2003, a law that recognizes the human right to migrate (law 25,871) was issued and included a section addressing Argentines abroad. What has been the impact, if any, of this framework? Has this recognition re-oriented state actions? By providing a review of the bibliography in Argentina, some programs and isolated actions, the current framework, agreements and actors, the report concludes that the legal framework has had little impact on public policies.